Formulation of hydrogel with synthetic polymers (PVA and PEG) - Shihab Ahmed, Afnan; Bakhtiar, M. Taher; Mandal, Uttam Kumar; Md. Jaffri, Juliana (2015)
Synthetic polymer hydrogels constitute a group of materials, utilized as a part of various biomedical fields, and are as yet producing for new encouraging applications. Physically cross-linked synthetic polymers, PVA and PEG, hydrogels are excellent materials owing to their biological tissue like nature. Transparent PVA and PEG hydrogels with varying polymer concentrations were obtained by using freeze-thaw method. gel fraction and swelling behavior were investigated. The gel fraction decreases with an increase in PEG content while the swelling ratio increases. Present study demonstrates a systematic variation in Gel fraction and swelling ratio of the developed hydrogel using the freezing–thawing method with PVA and PEG as a function of polymer concentration.